EVAS DEVICE EXPLANTATION IN A SECONDARY RUPTURE OF AN ABDOMINAL AORTIC ANEURYSM - Lopes, Alice (2020)
Endovascular aneurysm sealing (EVAS) was a relatively new concept that aimed to reduce the incidence of complications after endovascular aneurysm exclusion. However, EVAS device was recently recalled from market due to high risk of graft failure beyond two years after implantation(1,2). The aim of this paper is to report a case of a post-EVAS ruptured abdominal aortic aneurysm. A 72 year-old-man underwent EVAS and a bilateral sandwich technique of the iliac bifurcation for an aorto-bi-iliac aneurysm in 2015 in another institution. Follow-up CTA at three years showed a type Ib endoleak in the left iliac bifurcation and the patient was kept under clinical and imagiological surveillance (protocol unkown, again at another institution). Four years after the initial procedure the patient was admitted in the emergency department of our hospital after syncope and with abdominal pain. The CT-angiography (CTA) revealed a post-EVAS rupture in the distal aorta suggesting an endobag rupture (Fig 1). The patient underwent open surgical repair with explantation of the EVAS device (Fig 2 and 3) and an aorto-bifemoral interposition with a Dacron graft. The procedure was uneventful and the post-operative CTA showed a patent aorto-bifemoral graft without evidence of any complications (Fig. 4). One week later the patient was discharged home in good clinical condition. Post-operative surveillance is important in any aortic aneurysm endovascular procedure. However, since the last EVAS studies, all patients submitted to this technology must be under strict surveillance to identify complications like endobag rupture that can lead, as in the reported case, to aneurysm rupture which in turn can lead to stent graft explantation in an emergency setting